Health state utility values for metastatic pancreatic cancer using a composite time trade-off based on the vignette-based approach in Japan - Yuki Takumoto; Yuriko Sasahara; Hiroto Narimatsu; Tatsunori Murata; Manabu Akazawa (Health Economics Review, 2022)
Backgrounds Limited information is available on the utility values of metastatic pancreatic cancer, focusing on diferent health statuses, selected chemotherapy, and related grades 1/2 and 3/4 adverse events (AEs). We evaluated Japanese societal-based health-related utility values for metastatic pancreatic cancer by considering diferent grade toxicities commonly associated with chemotherapy using the vignette-based method. Methods We developed health status scenarios for patients with metastatic pancreatic cancer undergoing chemotherapy and conducted utility research using the developed scenarios in four steps: "literature review," "exploratory interview," "content validation", and "utility research". In the development process, to consider the impact of AEs of chemotherapy for metastatic pancreatic cancer on health state utility values, we selected neutropenia, febrile neutropenia, diarrhea, nausea and vomiting, and neuropathy as representative AEs. Each AE was classifed as either grade 1/2 or 3/4. We confrmed our created scenarios through cognitive interviews with the general population and clinical experts to validate the content. Finally, we developed 11 scenarios for using "utility research," evaluated in a societalbased valuation study using the face-to-face method. Participants for "utility research" were the general population, and they evaluated these scenarios in the composite time trade-of (cTTO) and visual analog scale (VAS) of the European quality of life (EuroQol) valuation technology to derive health state utility scores. Results Of 220 responders who completed this survey, 201 were adapted into the analysis population. Stable disease with no AEs (reference state) had a mean utility value of 0.653 using cTTO. The lowest mean utility score in the stable state was 0.242 (stable disease + grade 3/4 vomiting). VAS results ranged from 0.189 to 0.468, depending on the various grades of AEs in stable disease. In addition, grade 3/4 AEs and grade 1/2 nausea/vomiting were associated with signifcantly greater disutility. Utility values were also strongly infuenced by the direct impact of AE on physical symptoms, severity and their experience. In addition, 95.9% of the respondents agreed that they understood the questions in the post-response questionnaire. Conclusions We clarifed the health state utility values of patients with metastatic pancreatic cancer based on the general population in Japan. The efect on utilities should be considered not only for serious AEs, but also for minor AEs.
Keywords: 330; Utility; Metastatic pancreatic cancer; Health related quality of life; Time trade-of; Vignette-based method